Implementation of inclusive education for early childhood at RA Raudatul Athfal As-Sajdah Makkiyah North Pontianak - Azzahra, Nurma Annisa (Indonesian Journal of Multidisciplinary Educational Research, 2024)
Inclusive education is an educational service that includes children with special needs together with children their age in regular schools. RA As-Sajdah Makkiyah is one of the inclusive education programs in Pontianak City. Based on the results of observations, there is one deaf child in class A and several teachers who do not understand the existence of inclusive education because they are new teachers, so in class learning they do not use learning models that can help the teaching and learning process in inclusive classes. The research focus in this study is the implementation of inclusive education at RA As-Sajdah Makiyah Pontianak. Researchers use qualitative research. This research uses a qualitative approach with descriptive methods. Primary data in this research was obtained from direct interviews with school principals and teachers, while secondary data included documentation, RPPH and the curriculum implemented in schools. Data collection techniques in this research are observation, documentation and interviews. The results of RA As-Sajdah Makkiyah Pontianak's research used the 2013 curriculum adapted from the government, but for children with special needs, the class teacher made a modified curriculum according to the abilities of children with special needs. The approach to crew members is an individual approach. The learning process in terms of learning objectives and learning materials used is the same for regular children and ABK, the difference is that ABK do not have special accompanying teachers like other inclusive schools.